The socio legal significance of family waqf and its revival under state control - Sadique, Muhammad Abdurrahman (South East Asia Journal of Business Economics and Law, 2015)
Similar to waqf for the benefit of the general public, the numerous family awqaf in Islamic lands too played a key ole in upraising the economic standard of the society, as these catered to the needs of extensive families and clans for generations. Various degrees of restrictions on the creation or functioning of family awqaf in many countries have lead to their gradual disappearance. Faults and excesses of waqf managers that defeated the objectives of the waqf and resulted in unlawful enrichment have been cited among the main reasons for justifying the extension of state control. Family awqaf could be better managed based on an institutional format, while safeguarding their private and local nature. Providing the necessary legal regulation and executive framework protecting against misuse by administrators and others, while allowing their operation as decentralized autonomous institutions without state interference, have been suggested as means of reviving the role of family waqf.